Mechanical and nanomechanical properties of MWCNT/PP nanocomposite - K.I. Tserpes; A. Chanteli; Sp. Pantelakis; E.P. Koumoulos; C.A. Charitidis (Fracture and Structural Integrity, 2018)
The mechanical and nanomechanical properties of multi-walled carbon nanotube-reinforced polypropylene (MWCNT/PP) nanocomposite were investigated through tension tests (conducted on 2 wt% and 5 wt% specimens) and nanoindentation tests (conducted on 2 wt% specimens). In addition, the structural properties and topography of the nanocomposite were characterized by means of scanning electron microscopy (SEM) and Scanning Probe Microscopy (SPM), respectively. The results from the tension tests reveal an enhancement and a considerable scatter in the Youngs modulus and maximum stress of the MWCNT/PP nanocomposite for both MWCNT content. For the specimens with mechanical properties lower than the average values, the SEM and SPM images revealed poor dispersion and formation of large agglomerates. The hardness (as resistance to applied load) and Young蒒s modulus were mapped at 300 nm of displacement, for a grid of 70 ( 70 m2. Through projection, the resistance is clearly divided into 3 regions, namely the PP matrix, the interphase (region close to/between MWCNTs) and the regions of the MWCNT agglomerates. The resistance deviates from low values (few MPa) to 1.8 GPa. The present experimental study provides all necessary data for the model creation and validation of the MWCNT/PP nanocomposite.